Fungal Infection : Diagnosis and Management. - Richardson, Malcolm D. (John Wiley & Sons, 2011)
Fungal Infection: Diagnosis and Management, 4th Edition is a concise and up-to-date guide to the clinical manifestations, laboratory diagnosis and management of superficial, subcutaneous and systemic fungal infections. This highly acclaimed book has been extensively revised and updated throughout to ensure all drug and dosage recommendations are accurate and in agreement with current guidelines. A new chapter on infections caused by Pneumocystis jirovecii has been added. The book has been designed to enable rapid information retrieval and to help clinicians make informed decisions about diagnos.